Representative function of the prosecutor’s office: the current concept of court practice - Stefanchuk, Maryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article analyzes the trends in the development of the current concept of judicial practice regarding the representative function of the Public Prosecutor’s Office in Ukraine. It is stated that the representative function of the Public Prosecutor’s Office under the current legislative regulation is characterized by certain legal uncertainty and defects in such regulation, which leads to the formation of a practical understanding of the essence and mechanism of implementation of this function through the prism of legal positions of authorized law enforcement entities, mainly prosecutors and judges. It is established that the practice of applying the legislation on determining the object of prosecutorial representation and exceptional cases of such representation is dynamic and variable, and this necessitates its constant monitoring and legal analysis to identify trends in its development regarding the representative function of the Public Prosecutor’s Office. The author highlights the current trends in the development of the current concept of the prosecutor’s representative function through the prism of case law: the lack of a uniform understanding of the category «interests of the State» as an object of prosecutorial representation; recognition of the expanded interpretation of cases (grounds) for the prosecutor’s representation of the State’s interests in court as inconsistent with the principle of adversarial proceedings, which is one of the principles of justice; recognition of the mandatory condition for the prosecutor’s participation in the trial that he or she must substantiate the grounds for going to court with the introduction of a judicial standard for the prosecutor to prove inaction by the competent authority in protecting the interests of the state; formation of polar judicial concepts of the exclusivity of prosecutorial representation.